Enhancing nutrient translocation, yields and water productivity of wheat under rice–wheat cropping system through zinc nutrition and residual effect of green manuring. (29th July 2020) - Yadav, Devideen; Shivay, Y. S.; Singh, Y. V.; Sharma, V. K.; Bhatia, Arti
Abstract: Efficient nutrient and water use are two important considerations to obtain good harvests of wheat. This necessitates the development of an effective nutrient management technique that not only increases yield, but simultaneously can save nutrient and water use. In this context, a field experiment was conducted at Indian Agricultural Research Institute, New Delhi, India to evaluate the residual effect of sesbania and rice bean ( in-situ ), subabul ( ex-situ ) green manuring and Zinc (Zn) fertilization, using chelated Zn-ethylenediaminetetraacetic acid (Zn-EDTA) on nutrient use, yields and water productivity of wheat under rice–wheat cropping system. Among residual effects of green manure crops and Zn fertilization, sesbania and foliar spray of 0.5% chelated Zn-EDTA at 20, 40, 60 and 80 days after sowing (DAS) recorded significantly higher nutrient content and uptake and yields than other green manure crops and Zn treatments. Residual effect of sesbania saved about 46.5 × 10 3 and 30.5 × 10 3 L irrigation water per tonne of wheat over subabul and rice bean, respectively. Foliar spray of 0.5% chelated Zn-EDTA at 20, 40, 60 and 80 DAS saved about 55.5 × 10 3, 47 × 10 3 and 13 × 10 3 L irrigation water per tonne wheat over residual effect of 5 kg Zn ha −1 through chelated Zn-EDTA as soil application, 2.5 kg Zn ha −1 through chelated Zn-EDTA as soil application + 1 foliar spray of 0.5% chelated Zn-EDTA at flowering and foliar spray of 0.5% chelated Zn-EDTA at active tillering + flowering + grain filling, respectively. Correlation analysis showed positive correlation between Zn uptake and grain yield.